The Study of Social Media Contribution to Knowledge Sharing in Maqasid Al-Shariah - Zailan, Siti Nur Syamimi; Noordin, Mohamad Fauzan (International Journal on Perceptive and Cognitive Computing, 2025)
The need to obtain information quickly has driven the development of social media technology innovation and the establishment of digital communications. People around the world use social media extensively as they see it as an important tool in their daily lives. In organizations, Knowledge has always been a valuable resource. As social media becomes more advanced, it can be one of the tools for sharing knowledge or information. However, in terms of content and connectivity, Social Media usage for information sharing has produced a difficult circumstance. According to research by Shompa et al. [35], a person should be careful to use social media properly from an Islamic viewpoint. Inappropriate Social Media usage causes otherwise to take us away from Allah and His command. Despite the social benefits provided by social media, it may create a burden for the user. It may create some issues that are incompatible with Maqasid Al-Shariah (Islamic objectives), such as fake news, misinformation, malinformation, violation of privacy, incitement to hatred, some electronic fraud, children’s extortion, and people’s negative judgment. In this research, the researcher will present the contribution of social media to knowledge sharing and the Islamic objectives of the Protection of Aql (Mind/intellect). To protect the intelligence on Social Media, by spreading false knowledge-related material and throwing derogatory comments against those in disagreement that can harm their intellect, Muslims are ordered to prevent evil actions.